PENGARUH MOTIVASI INTRINSIK DAN MOTIVASI EKSTRINSIK TERHADAP KINERJA PEGAWAI KANTOR CAMAT KECAMATAN ILIR TIMUR I KOTA PALEMBANG - Endrianto, Tarmizi (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
This research was conducted using quantitative methods through a questionnaire distributed to 42 respondents as a sample number that has been determined for the population of employees in the District Office of Ilir Timur I Palembang City which amounted to 42 employees. This study uses data analysis by testing the Validity and Reliability through SPSS and determine the value of correlation and multiple linear regression using the help of SPSS version 20. The results of this study show that intrinsic motivation and extrinsic motivation simultaneously (together) have a significant effect on the employee performance of Ilir Timur I District Office, Palembang. It is known in the test results that the value of F is calculated as 280,560> F table is 3.24 with sig 0.000 <0.005. The results of the t test show that extrinsic motivation (X2) is more influential than the intrinsic motivation seen from the value of T X2 is greater than T X1. (23,399> 0.556).Â Based on the calculation of the multiple linear regression equation of intrinsic motivation and extrinsic motivation on employee performance, namely Y = -2,545 + 0.027X1 + 1,076X2, this states that if the variables of intrinsic motivation and extrinsic motivation are considered constant or 0 (zero), thenemployee performance will increase by -2,545. As well as hypothesis testing with an R Square result of 0.935 (93.5%) both variables affecting employee performance have a very strong influence, and the remaining 6.5% are influenced by other factors that are not thorough.This indicates that intrinsic motivation and extrinsic motivation affect employee performance. Where if the intrinsic motivation and extrinsic motivation are high then it will improve the performance of the employee optimally and the goals of the agency will be achieved